Rapidoxy® 100: A Solvent-Free Pre-treatment for Production of Canolol - Nandasiri, Ruchira; Imran, Afra; Thiyam-Holländer, Usha; Eskin, N. A. Michael (Frontiers in Nutrition, 2021)
RapidOxy® 100 is an automated instrument originally designed for measuring the oxidative stability of both solid and liquid samples. The compact and portable design of RapidOxy® 100, and its built-in pressurized heating chamber, provide a suitable environment for studying processing conditions. The feasibility of using oxygen or an inert atmosphere provides the ideal environment to study the effect of dry heat pre-treatment on canola antioxidants. The current study used RapidOxy® 100 to examine the impact of pressurized dry heat pre-treatment, under nitrogen, on the ultrasonic extraction of phenolic compounds. The effect of different pre-treatment temperature-time combinations of 120, 140, 160, and 180oC for 2, 5, 10, 15, and 20 minutes on the subsequent extraction of canola phenolic compounds was examined. The major sinapates identified by HPLC were sinapine, sinapic acid, and canolol. The optimum RapidOxy® condition for the maximum recovery of canolol was 160oC for 10 minutes. RapidOxy® 100 proved to be a novel and versatile instrument for enhancing the extraction of phenolic compounds.